Pembelajaran Menulis Teks Prosedur Pada Siswa Kelas XI SMA Dengan Menggunakan Metode Discovery Learning Berbantuan Aplikasi Sparkol Videoscribe - Ahmad Nur Faizi (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Writing procedure texts is still considered normal and has not shown things that express students' creativity in developing ideas and ideas in a procedure text. The purpose of this study was to determine student responses, student learning outcomes and student difficulties in learning to write procedural texts using the discovery learning method assisted by the Sparkol Videoscribe application. The use of the sparkol videoscribe application or what we are familiar with the moving whiteboard is useful for writing procedural texts. The method used in this research is a qualitative descriptive method. Data collection techniques in the form of tests and questionnaires. The success of learning is seen from the results of the knowledge and skills test which shows the average value of both of them is 81.7 and has met the achievement indicators. The difficulty of knowledge test questions with a score of 11 regarding commands shows the structure of the procedure text in the steps section, while the difficulty of skills questions with a score of 64 is found in the language rules of persuasive statements. The results of the response were very good during the learning process by showing the percentage of 81%. Judging from student learning outcomes and the results of student responses, the methods and application of assistance used can improve students' learning to write procedural texts.